The Conditions of Success: a Change in Bowness Model - Harillo Pla, Adrià (Vilnius University Open Series, 2022)
This text presents a reformulation of the model that Alan Bowness — former director of the prestigious London’s Tate Gallery — used to represent the way in which an artist achieves success. The reasons why the modification of the cited model seems coherent are presented from a theoretical and pre-experimental perspective. The results intend to be coherent and plausible. Nevertheless, they are generic and can differ in different specific contexts. Our conclusion is that Bowness model is outdated and does not show the current paradigm of art and its market, being this reformulation necessary. On the other hand, it must be clarified that when we refer to ‘success’, we are referring to a success which is primarily economic, or derivate from the economic one.
Keywords: Art Market; Art World; Artist; Bowness; Institutional Theory